2021
DOI: 10.1103/physrevb.104.174419
|View full text |Cite
|
Sign up to set email alerts
|

Giant topological Hall effect in centrosymmetric tetragonal Mn2xZnxSb

Abstract: Topological magnetism typically appear in non-centrosymmetric compounds or compounds with geometric frustration. Here, we report the effective tuning of magnetism in centrosymmetric tetragonal Mn 2−x Zn x Sb by Zn substitution. The magnetism is found to be closely coupled to the transport properties, giving rise to a very large topological hall effect with fine tuning of Zn content, which even persists to high temperature (∼ 250 K). The further magnetoentropic analysis suggests that the topological hall effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
3
6
0
Order By: Relevance
“…The contour mapping shows that a large ρ T persists up to room temperature around the field of 0.1 T and it converges to zero above the field of %0.3 T. Such behavior has been observed in similar systems due to fully spin-polarized state at higher magnetic field. [24,25,30,[33][34][35][38][39][40]42] The comparison with the previously reported bulk systems [4,12,19,30,35,[59][60][61][62][63][64][65][66][67][68][69][70] (Figure 2e) indicates that the large topological Hall persists in the wider temperature range of 2-300 K, which make the Mn 2 CoAl compound an ideal candidate for the spintronic applications. The moderate decrease in the maximum ρ T with temperature can be ascribed to the microscopic noncoplanar spin texture.…”
Section: Topological Hall Analysissupporting
confidence: 66%
“…The contour mapping shows that a large ρ T persists up to room temperature around the field of 0.1 T and it converges to zero above the field of %0.3 T. Such behavior has been observed in similar systems due to fully spin-polarized state at higher magnetic field. [24,25,30,[33][34][35][38][39][40]42] The comparison with the previously reported bulk systems [4,12,19,30,35,[59][60][61][62][63][64][65][66][67][68][69][70] (Figure 2e) indicates that the large topological Hall persists in the wider temperature range of 2-300 K, which make the Mn 2 CoAl compound an ideal candidate for the spintronic applications. The moderate decrease in the maximum ρ T with temperature can be ascribed to the microscopic noncoplanar spin texture.…”
Section: Topological Hall Analysissupporting
confidence: 66%
“…[9][10][11][12] Very recently, Nabi et al observed a giant composition-tunable topological Hall effect up to B250 K in Mn 2-x Zn x Sb single crystals, which is caused by topological magnetic spin texture, suggesting that Mn 2 Sb-based compounds are good candidate materials for studying topological magnetism. 13,14 These results demonstrate that Mn 2 Sb-based compounds are good platforms for the fundamental study of interplay among the spin, charge, and lattice degrees of freedom.…”
Section: Introductionmentioning
confidence: 78%
“…It is worthwhile to mention here that intrinsic AHE is expected to dominate in the overall behaviour of AHE, when the longitudinal conductivity of sample lies in the good metallic regime i.e. σ xx is an order of 10 4 -10 6 S/cm [1,15,16,43,46]. Our system shows the deviation from this criterion as the extrinsic AHE has significant contribution in the AHE despite the σ xx is an order of 10 4 S/cm.…”
Section: (E)mentioning
confidence: 67%